2001
DOI: 10.1677/joe.0.1680221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gs alpha mutations in Korean patients with pituitary adenomas

Abstract: The reported frequencies of Gs mutations (gsp mutations) in growth hormone (GH)-secreting pituitary adenomas are variable (ranging from 4·4 to 43%), and the presence of these mutations in the other pituitary adenomas is still a matter of controversy. Previous clinical and biochemical analyses of patients with GH-secreting pituitary adenomas and gsp mutations produced conflicting results and did not demonstrate obvious characteristics. Therefore, we investigated the prevalence of gsp mutations in Korean patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
4
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 21 publications
5
35
4
1
Order By: Relevance
“…In terms of somatic DNA alterations, GSP oncogeneactivating mutations are the most frequently encountered (Landis et al 1990). Higher expression of the GSa protein, either in GSP-positive adenomas or in GSP-negative ones, is associated with smaller adenomas (Landis et al 1990, Spada et al 1990, Kim et al 2001, Picard et al 2007. GSP-positive adenomas seem to have higher GH secretion and better response to somatostatin analogs (Spada et al 1990, Barlier et al 1998.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of somatic DNA alterations, GSP oncogeneactivating mutations are the most frequently encountered (Landis et al 1990). Higher expression of the GSa protein, either in GSP-positive adenomas or in GSP-negative ones, is associated with smaller adenomas (Landis et al 1990, Spada et al 1990, Kim et al 2001, Picard et al 2007. GSP-positive adenomas seem to have higher GH secretion and better response to somatostatin analogs (Spada et al 1990, Barlier et al 1998.…”
Section: Discussionmentioning
confidence: 98%
“…Although this analysis was not done in patient #2, the fact that patient #1 is gsp positive increases her chance to be successfully controlled with octreotide LAR ® . In fact, several studies explored SA responsiveness in the light of gsp status and it seems that gsp positive patients are better responders (20)(21)(22)(23)(24)(25)(26), although there is some controversy in the literature (18).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical detection of somatostatin receptor subtype 2 (SSTR2) correlates positively with percent GH reduction on acute test and IGF-I after 6 months of treatment (18,19). When molecular analysis of the ressected tumor is possible, the presence of the gsp oncogene seems to be indicative of a good response to SA treatment (20)(21)(22)(23)(24)(25)(26). Despite the fact that most studies suggest that gsp-positive adenomas respond better to octreotide LAR ® compared to gsp-negative tumors, a recent study failed to fi nd differences in octreotide LAR ® sensitivity according to gsp status (18).…”
Section: Introductionmentioning
confidence: 99%
“…The recurrent somatic mutations in GNAS gene coding for the α-subunit of the stimulatory G protein Gs, commonly named gsp mutation, have been associated with particular clinical characteristics: smaller and less invading densely granulated tumours, normally appearing in older patients (Landis et al 1990, Spada et al 1990, Faglia et al 1996, Yang et al 1996, Barlier et al 1998, Kim et al 2001, Freda et al 2007). The implication of gsp mutation in SSA response has been widely discussed (Larkin et al 2013); nevertheless, a recent meta-analysis revealed that GNAS-positive patients have an approximately 10% greater reduction in GH levels in response to an acute octreotide suppression test (Efstathiadou et al 2015).…”
Section: Gnas Mutationmentioning
confidence: 99%